THE ANTECEDENTS OF ELECTRONIC WORD OF MOUTH RESPONSES IN HOTEL EXPERIENCE EVALUATION - Basri Rashid; Han Chao; Nor Rabiatul Adawiyah Nor Azam (School of Tourism, Universitas Ciputra Surabaya, 2021)
In today’s digital information era, it is common for hotels guests to share their visit experience to their acquaintances or public online especially on popular social media platforms. Hence, reviews and experience sharing have moved from the traditional words of mouth to the electronic word of mouth (eWOM). This paper aims to develop and propose a testable research framework for assessing hotel guests’ experience and their eWOM responses. Methodically, desk research was carried out by conducting an exhaustive review of past literature to establish a theoretical understanding of hotel experience assessments and to determine the variables and their measurements. Meaningful encounters with the hotel’s products and services are summed up as consumption experience in the forms of perceived value and satisfaction. This cumulative experience may entice the guests to upload their responses on digital platforms. Theoretically, the proposed framework reduces the gaps related to the formulation of research constructs for hotel visit experience assessment. Practically, this paper offers hotel operators a testable framework that can guide them in the development of survey materials in order to gain a comprehensive understanding about their guests visit experience assessment and their electronic word-of-mouth response.